The abortive revolution : China under Nationalist rule, 1927-1937 - Eastman, Lloyd E. (Harvard East Asian monographs ;, 1990)
An in-depth investigation of selected aspects of Chinese history during the Nanking Decade, illuminating the forces that prevented the re-creation of national unity and vitality under Chiang Kai-sheck and the Kuomintang nationalists.